THE INFLUENCE OF COMPLEX THERAPY ON THE INFLAMMATORY MARKERS OF PATIENTS WITH SECONDARY OSTEOARTHRITIS - I. A. Starodubtseva (Архивъ внутренней медицины)
The aim of the study is to evaluate the efficacy of complex therapy of secondary osteoarthritis in patients with rheumatoid arthritis with the use of inhibitor of interleukin-1, including the dynamics of inflammatory markers.Materials and methods: 248 patients with secondary osteoarthritis in rheumatoid arthritis were involved in the trial. The participants were divided into 4 groups: patients of group I took inhibitor of interleukin-1 (diacerein) in combination with laser therapy and methotrexate; inhibitor of interleukin-1 in complex with methotrexate took patients from group II; group 3 — laser therapy + methotrexate and patients of group IV took only methotrexate. The efficacy of therapy we estimated in 6 months.Results: The constructed model surfaces indicated the decreased levels of IL-1, COMP and DAS 28 in group 1 till 6,68±0,37 pg/ml (p<0,001), 16,92±0,8 ng/ml х 10² (p<0,001) и 2,06±1,19 (p<0,05) accordingly in comparison with groups III and IV. Also the model surfaces revealed the interdependency of all these indicators. The control group (IV) reacted to the treatment by decreasing the indicators as well. However, the dynamics of the changes was significantly less. In patients of groups I and II the levels of ESR and CRP decreased to 13,95±0,52* (*p<0,001) and 10,97±0,43* (*p<0,001); 16,53±0,63* (*p<0,001) and 12,81±0,77* (*p<0,001) accordingly.Conclusions: In comparison analysis we noted statistical significant advantages (p<0,01) of the use of diacerein with methotrexate regarding the dynamic of IL-1 and COMP, ESR, CRP in patient’s serum, which is accompanied by the reduction of basic disease activity on DAS 28.